MODAL SOSIAL DAN BUDAYA DALAM PEMBANGUNAN DESA - Rosaliza, Mita (Universitas Lancang Kuning, 2016)
In the concept of Nawa Cita, “developing village and urban,” ex transmigration village has important role as initiator in developing economic area and it is expected to be able to create relation (bridging) and contribute in the development of surrounding areas. This research is triggered by that idea, so its aims are to describe : how can the social capital push the development of the area through the perspective of ex transmigration village and local village (bonding)?, how is the bridging- linking pattern created between ex transmigration village and local village, how is linking created institutionally between ex transmigration village and local and central governments. This research conducts qualitative and simple quantitative analysis with the case study of 104 villages (24 ex. Transmigration villages, 80 local villages) in Pelalawan Regency, Riau Province. This research uses potential data and level of village development and level of village poverty and strengthened by related researches and later it is analyzed in descriptive analysis. The result shows that ex transmigration villages develop well, better then local village due to the existence of strong social capital bonding. In other side, the development of village area of ex transmigration village is enclaved and the bridging with the local village is not created, which leads to imbalance development between ex transmigration program which brings ex-transmigration village having better competitive ability.